Analysis of Construction Project Duration Acceleration Through Workforce Addition Using the Crashing Method at SD Negeri 2 Murtajih Building - Anggatha Misykat Alamsyah; Budi Witjaksana; Jaka Purnama (Transpublika Publisher, 2025)
Delays in the completion of construction projects remain a major problem, particularly in the construction and rehabilitation of educational buildings, which require precision in terms of time, cost and quality. One effort to address this problem is accelerating the project duration through the crashing method. Therefore, this study aims to analyze the acceleration of construction project duration through the addition of workforce using the crashing method in the rehabilitation project of SD Negeri 2 Murtajih, Pamekasan Regency. The research method used is a quantitative descriptive method with a case study approach, using secondary data in the form of a time schedule, budget plan (RAB), S curve, and project progress reports. The analysis was conducted by determining normal workforce productivity, crashing productivity, normal duration, crash duration, and the percentage of time acceleration due to the addition of workforce. The results showed that adding workers significantly accelerated the implementation duration. For instance, in the brick wall and tile floor installation, which had a normal duration of 10 days, adding 15 workers resulted in a crash duration of 7 days with an acceleration of 33%, while adding 17 workers resulted in a crash duration of 6 days with an acceleration of 41%. In conclusion, the crashing method proved effective in accelerating the project duration, despite impacting increased workforce costs. Thus, optimal acceleration planning is required to achieve a balance between time savings and additional costs for more efficient and economical project implementation.